Affirmative action policy in developing countries: Lessons learned and a way forward - Elizabeth Kaletski; Nishith Prakash (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
There are several countries who have responded to concerns regarding historically disadvantaged groups, particularly ethnic and racial minorities and women, with not only anti-discrimination legislation, but also affirmative action policies. Although these policies are seemingly well intentioned, there continues to be little consensus about their actual impact. This paper seeks to examine the current state of the literature on one specific affirmative action policy, political reservation in India. The Indian constitution mandates seats be reserved at various levels of government for political representation of Scheduled Castes, Scheduled Tribes and women. This paper discusses the existing inequalities across these groups, along with the basic theory behind political reservation in fixing these inequalities, while also recognizing that theory provides many channels through which affirmative action policy can impact a variety of outcomes. Thus we turn to the vast empirical literature on the topic to shed light on what can be learned from the Indian context and how future policy can be reformed and shaped based on these experiences.
Keywords: J15; J18; J71; J78; 330; affirmative action; minorities; India